Implementation of Performance “Si Cantik” in BKPSDM Kabupaten Bogor - Prastowo, Bramastyo Bontas; Yofita Rahayu, Aprianti (International Journal Labs, 2025)
This research aims to identify the process of implementing Si Cantik in the ASN Performance Assessment at BKPSDM Bogor Regency. This research uses a qualitative case study approach. The data collection technique through interviews and analysis tools used was the Edward III 1980 Models. The key informants in this research were performance analysts and sub-coordinators for the evaluation and assessment of apparatus performance at Human Resources Development Agency Bogor Regency. The results of this research by reviewing the implementation of the 4 aspects of the Edward Model, namely communication, resources, disposition, and bureaucratic structure, in general, it can be said to be good, but there are still aspects that are less than optimal and need improvement to be more optimal, namely in the structural aspect bureaucracy where the SOUP for command center flow has not been properly documented. Even though in general the Si Cantik implementation process is good, there is still a need for suggestions for improvement in the utilization of Si Cantik which include, regular monitoring and evaluation can be carried out regarding the Si Cantik communication process, adding Si system managers, active involvement and participation of superiors and adapt strategies that suit the agency's internal capabilities in dealing with employee resistance and dynamics, and can add to the flow or work procedures for the problem complaint process, namely creating clear or detailed SOPs or technical instructions so that the flow can run well with the command center.